Corrosion resistance of multilayer coatings deposited by PVD on inconel 718 using electrochemical impedance spectroscopy technique - Gaona Tiburcio, Citlalli; Montoya Rangel, Marvin; Cabral Miramontes, José Ángel; Estupiñan López, Francisco Humberto; Zambrano Robledo, Patricia del Carmen; Orozco Cruz, Ricardo; Chacón Nava, José G.; Baltazar Zamora, Miguel Ángel; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2020)
AlCrN/TiSi, AlCrN/TiCrSiN and AlCrN/AlCrN + CrN coatings were deposited on Inconel 718 alloy by physical vapour deposition (PVD). The corrosion behaviour of uncoated and coated specimens was evaluated using electrochemical impedance spectroscopy (EIS) at open circuit potential in a 3.5 wt.% NaCl and 2 wt.% H2SO4 solutions. The EIS data acquired were curve fitted and analysed by equivalent circuit models to calculate the pore resistance, the charge transfer resistance and the capacitance. The Nyquist diagrams of all systems showed one part of the semicircle which could relate that reaction is a one step process, except for the AlCrN/TiCrSiN and AlCrN/AlCrN + CrN coatings in H2SO4 solution, for which two semicircles related to active corrosion in substrate alloy were found. However, from the Bode plots, it was possible to identify two the time constants for all systems exposed to NaCl and H2SO4 solutions. According to electrochemical results, the corrosion resistance of the AlCrN/TiSiN coating was better in the NaCl solution, whereas the AlCrN/AlCrN + CrN coating show better performance in the Sulphuric Acid solutions.